‘Newton was heel exact wetenschappelijk – ook in zijn chemische werk’. Nederlandse wetenschapsgeschiedenis in niet-wetenschapshistorische tijdschriften, 1977-2017 - Beckers, Danny; Beckers, Anne (Studium, 2019)
Both historians of science and scientists write papers that are published under a "historical" denominator in non-specialist journals, such as the journals for professional scientists and teachers. This paper focuses on the various motives for these publications, thereby illustrating both the enormous enthusiasm for our work outside of circles for professional historians, as what is conceived as crucial in our work to people outside of our field.